Ki-67 Antigen Overexpression Is Associated with the Metaplasia-Adenocarcinoma Sequence in Barrett's Esophagus. (11th July 2012) - Volkweis, Bernardo Silveira; Gurski, Richard Ricachenevsky; Meurer, Luise; Pretto, Guilherme Gonçalves; Mazzini, Guilherme da Silva; Edelweiss, Maria Isabel
Abstract : Introduction . The objective of this study was to evaluate Ki-67 antigen expression in patients with Barrett's esophagus and esophageal adenocarcinoma and to assess its correlation with the metaplasia-esophageal adenocarcinoma progression. Methods . Using immunohistochemistry we evaluated the Ki-67 index in patients with Barrett's esophagus, esophageal adenocarcinoma, and controls. We included patients with endoscopically visible columnar mucosa of the distal esophagus (whose biopsies revealed specialized intestinal-type metaplasia), patients with esophageal and esophagogastric tumors types I and II, and patients with histologically normal gastric mucosa (control). Results . In the 57 patients studied there were no statistically significant differences between the groups with respect to age or race. Patients with cancer were predominantly men. The Ki-67 index averaged 10 ± 4 % in patients with normal gastric mucosa (n = 17 ), 21 ± 15 % in patients with Barrett's esophagus (n = 21 ), and 38 ± 16 % in patients with cancer (n = 19 ). Ki-67 expression was significantly different between all groups (P < 0.05 ). There was a strong linear correlation between Ki-67 expression and the metaplasia-adenocarcinoma sequence (P < 0.01 ). In patients with cancer, Ki-67 was not associated with clinical or surgical staging. Conclusions . Ki-67 antigen has increased expression along the metaplasia-adenocarcinoma sequence. There is a strong linear correlation between Ki-67 proliferative activity and Barrett's carcinogenesis.